Market Reaction to International Investment Announcements of Malaysian Firms: Illusion or Reality - Bany Ariffin; D. Agus Harjito (Management Development Centre (MDC) Department of Management, Faculty of Business and Economics Universitas Islam Indonesia, 2004)
This research substantiates evidence on the efficiency of one of the fastest developing and largest emerging securities market (Kuala Lumpur Stock Exchange) in the Asia Pacific rim with respect to foreign investment announcements. Specifically, in this study we are interested in finding out whether or not: (1) foreign investment announcement is relevant information and market reacts toward it and (2) what forms of market reaction does this information produce. Our study focuses on international investment announcements made in 1990 through 2000 for firms listed on the main board of the Kuala Lumpur Stock Exchange (KLSE) of Malaysia. The result shows that the announcements of foreign investment produce a significant positive daily abnormal return surrounding the event period. This implies that foreign investment announcements do contain new relevant information and thus move the market. In addition, investors also generally react favorably to the international investment efforts of Malaysia firms listed at KLSE. This is evidenced by the significant positive reaction of the market to announcement of investments in foreign countries. The t-statistic for the fourteen days, prior and fourteen days after the announcement indicate non-significance abnormal returns. Since none of the abnormal return is statically significant for each one of the fourteen days before and after the event period, it seems that the market reflects this new information (foreign investment announcements) rather efficiently.Keywords: market reaction, international investment announcement, relevant information.